Electrical and Optical Properties of Nickel‐Oxide Films for Efficient Perovskite Solar Cells. Issue 9 (9th August 2020) - Hossain, Mohammad Ismail; Hasan, A. K. Mahmud; Qarony, Wayesh; Shahiduzzaman, Md.; Islam, M. A.; Ishikawa, Yasuaki; Uraoka, Yukiharu; Amin, Nowshad; Knipp, Dietmar; Akhtaruzzaman, Md.; Tsang, Yuen Hong
Abstract: Efficient hole transport layer (HTL) is crucial for realizing efficient perovskite solar cells (PSCs). In this study, nickel‐oxide (NiOX ) thin‐films are investigated as a potential HTL for PSCs. The NiOX films are prepared by electron‐beam physical vapor deposition at low temperatures. The crystalline properties and the work function are determined by X‐ray diffraction and photoelectric yield spectroscopy. The transmission and the complex refractive index of the films are determined by optical spectroscopy and ellipsometry. Furthermore, PSCs are fabricated and characterized. The short‐circuit current density ( J sc ) of the PSC is limited by the optical loss due to the NiOx front contact. The optical losses of the front contact are quantified by optical simulations using finite‐difference time‐domain simulations, and a solar cell structure with improved light incoupling is designed. Furthermore, the electrical characteristics of the solar cell are simulated by finite element method simulations. As a result, it is found that the optical losses can be reduced by 70%, and the light incoupling can be improved so that the J SC can be increased by up to 12%, allowing for the realization of PSCs with an energy conversion efficiency of 22%. Findings from the numerical simulations are compared with experimentally realized results. Abstract : A multi‐layer front contact system is investigated for efficient perovskite solar cells, which allows for realizing improved light incoupling by reducing the optical losses. The front contact consists of a thin nickel‐oxide (electron‐beam vapor physical deposition‐grown), and a thick pyramidal textured zinc‐oxide (metal‐organic chemical vapor deposition‐grown) layers. Optics and electrical characteristics of solar cells are investigated by 3D electromagnetic simulations.